Post-Crisis Fiscal Policy Priorities for the ASEAN-5. (IMF Working Papers; Working Paper ;, 2010)
This paper focuses on post-crisis fiscal priorities in the ASEAN-5 economies - Indonesia, Malaysia, Philippines, Singapore and Thailand. Sound economic fundamentals and timely and forceful policy responses to the crisis, including fiscal stimulus, contributed to rapid economic recovery in the ASEAN-5. As growth rebounds, these economies are beginning to identify, communicate and implement their strategies for unwinding the fiscal stimulus while addressing long-term growth challenges. In this context, the paper highlights the need for fiscal policies to address infrastructure gaps, stimulate private consumption and expand social safety nets. Creating fiscal space to address these challenges will require raising revenues and reorienting public spending rather than increasing borrowing. Supporting structural reforms, aiming to stimulate private infrastructure investment, could help address long-term growth challenges, while easing the burden on fiscal policy.